Auditor Independence through the Lens of Islamic Values: A Phenomenological Approach - Sari, Nur Rahmah; Juardi, Muhammad Sapril Sardi (Journal of Economic Education and Entrepreneurship Studies, 2025)
Independence serves as a fundamental ethical pillar of the auditing profession, ensuring the credibility of financial statements and maintaining public trust. However, in practice, auditors frequently encounter professional, structural, and emotional pressures that challenge their commitment. This study aims to interpret the meaning of auditor independence, both internal and external, through the lens of Islamic values. Employing a transcendental phenomenological approach within an interpretive paradigm, data were obtained through in-depth interviews with four auditors representing various institutions, including two Public Accounting Firms, the Audit Board of Indonesia, and internal audit units within higher education institutions. The findings indicates that independence is perceived not merely as compliance with technical standards but as a form of self-restraint, trustworthiness (amanah), and spiritual awareness. Islamic values such as honesty, steadfastness (getteng), and accountability before God serves as moral safeguards against temptation and conflicts of interest. The study underscores that the meaning of independence is multidimensional, which are ethical, spiritual, and contextual, and highlights the need for a holistic approach to reinforcing professional ethics in auditing. These insights provides important implications for developing value-based auditor education curricula and institutional policies aimed at fostering sustainable professional integrity.